Numerical Simulation Studies on Stall Suppression of a NACA0015 Airfoil - Shrestha, Biswash; Bhattarai, Nawraj (Journal of Advanced College of Engineering and Management, 2021)
This study aims to achieve an improved airfoil performance at low Reynolds number, and to determine the optimum position and size of rectangular cross-section burst control plate (BCP) to suppress stall in airfoil. The type of airfoil used in the present study is NACA0015 (National Advisory Committee for Aeronautics) airfoil with 200 mm of chord (c) length. Here, rectangular cross-section burst control plates with different sizes and at different locations are investigated numerically at the low Reynolds number of 1.6×105. Total of three positions (0.05c, 0.1c and 0.2c from the leading edge of airfoil), and four sizes (with heights 0.3 mm, 0.7mm, 1mm and 1.5 mm, and constant width 4 mm) of rectangular BCPs are simulated in ANSYS Fluent software using Transition SST model. The results indicate that the rectangular cross-section burst control plate is an effective device in the suppression of airfoil stall. For 0.7 mm and 1 mm height BCPs, the stall angle is postponed by 2° for all positions, while for 0.3 mm and 1.5 mm height BCPs, the reduction in sudden fall of lift can be observed but at the cost of reduction in maximum lift coefficient. Among various configurations, the 1mm height BCP located at 0.2c position is found to be most effective in the suppression of stall.